Penerapan Aspek Kompetensi Administrasi, Transparansi Dan Efisiensi Dalam Restrukturisasi Birokrasi Pemerintah Daerah (Institut Pemerintahan Dalam Negeri, 2019)
Abstrack The implementation of the restructuring of the bureaucracy can be defined as a process of redesigning or rearrangement of the existing bureaucracy. When the dynamics on both internal and external environments that bureaucracy must also adapt these dynamics in order to survive. Adaptation to the dynamics of the causes of bureaucracy must perform in accordance with reality. Restructuring or realignment of bureaucratic organization is essentially an activity to prepare the unit will be assigned the bureaucratic organization of work areas, specific tasks or functions. Government Regulation No. 41 of 2007 is a government regulation governing guidelines for the preparation and control of the regional organization in the overall governance process. Kata kunci: good governance, bureaucracy restructurization, local government